The results of the study of pharmacists' opinion regarding the organization of their work in pharmacies during the coronavirus COVID-19 pandemic - B. P. Hromovyk; M. V. Korolyov (The State Expert Center of the Ministry of Health of Ukraine, 2020)
Since the beginning of the quarantine, pharmacists, especially those who work in pharmacies, are at the forefront of the fight against COVID-19 coronavirus infection, and they do their best to provide quality pharmaceutical assistance. The aim of the study was to study the opinions of pharmacists on the organizational features of their work in pharmacies during quarantine associated with the coronavirus COVID-19 pandemic. The methods of survey, mathematical statistics, generalization and interpretation of the results are used. 499 pharmacists from 25 regions of Ukraine except for territories not controlled by the Government, were interviewed. The study was conducted from 7 to 19 April 2020. Pharmacists' anxious expectations and pessimistic sentiments elucidated through the COVID-19 coronavirus have been. It is shown that social distance in pharmacies is primarily aimed at limiting the number of people admitted to the pharmacy at the same time, then - to install a protective screen in the sales hall, as well as its planning. It has been found that pharmacists often have to deal with inappropriate visitor behavior. The increase of physical load of pharmacists, the main reason for which is the peculiarities of working with visitors during social distance, as well as finding a large part of them under constant psychological pressure, is revealed. The degree of concern of pharmacists through the Covid-19 coronavirus, the availability of various safety measures in pharmacies, the levels of aggressive behavior on the part of pharmacy visitors, exercise stress and being under constant psychological pressure from pharmacists have been established.